Differential Homeostasis of Sessile and Pendant Epithelium Reconstituted in a 3D‐Printed "GeminiChip". Issue 28 (12th May 2019) - Cai, Pingqiang; Li, Zhuyun; Keneth, Ela Sachyani; Wang, Luying; Wan, Changjin; Jiang, Ying; Hu, Benhui; Wu, Yun‐Long; Wang, Shutao; Lim, Chwee Teck; Makeyev, Eugene V.; Magdassi, Shlomo; et al.
Abstract: Local mechanical cues can affect crucial fate decisions of living cells. Transepithelial stress has been discussed in the context of epithelial monolayers, but the lack of appropriate experimental systems leads current studies to approximate it simply as an in‐plane stress. To evaluate possible contribution of force vectors acting in other directions, double epithelium in a 3D‐printed "GeminiChip" containing a sessile and a pendant channel is reconstituted. Intriguingly, the sessile epithelia is prone to apoptotic cell extrusion upon crowding, whereas the pendant counterpart favors live cell delamination. Transcriptome analyses show upregulation of RhoA, BMP2, and hypoxia‐signaling genes in the pendant epithelium, consistent with the onset of an epithelial–mesenchymal transition program. HepG2 microtumor spheroids also display differential spreading patterns in the sessile and pendant configuration. Using this multilayered GeminiChip, these results uncover a progressive yet critical role of perpendicular force vectors in collective cell behaviors and point at fundamental importance of these forces in the biology of cancer. Abstract : A multilayer "GeminiChip" is 3D printed to reconstitute the sessile and pendant epithelium. This allows for understanding of the role of cryptic transepithelial stresses in the mechanogenetic regulation of tissue‐level homeostasis, which imparts the former with preference toward apoptotic extrusion and the latter toward live delamination, emerging through the dichotomous epithelial tension evolution and genetic expression.